Seven Principles for Mobilizing Open Data to Power India's Agri-Stack - Mothkoor, Venugopal; Venugopal, Murali Krishna; Koganti, Dharani Kanth; Akshatha, Annaiah; Sharma, Sheetal; Patwar. Shelly; Koo, Jawoo (2022)
Digitalization is transforming existing agricultural business processes and services and enabling new means to deploy innovative services and products at scale. At the core of these services and innovations is open data. In India, a lot of work has been done by the Central and State Governments, academic, research institutions, and the private sector in conceptualizing different approaches and aspects of an "Agri-Stack" to digitally transform agriculture. Recognizing the need to integrate these efforts and incorporate use cases, CGIAR Research Initiative on Digital Innovation, in partnership with The Agri Collaboratory (TAC), organized a consultation workshop in Delhi in November 2022. Participated by 70 stakeholders representing 54 organizations, the workshop enabled in-depth discussion on the design principles of thematic use cases and facilitated a broader debate on the specific building blocks needed. This document summarizes key principles discussed throughout the workshop.